2022
DOI: 10.1371/journal.pone.0266595
|View full text |Cite
|
Sign up to set email alerts
|

Time to under-five mortality and its predictors in rural Ethiopia: Cox-gamma shared frailty model

Abstract: Background Under-five mortality (U5M) is one of the most important and sensitive indicators of the health status of the community. Despite there having been a substantial reduction in U5M since 1990, its rate is still high in Sub-Saharan African countries. Thus, this study aimed to assess time to under-five mortality and its predictors in rural Ethiopia. Methods This study utilized a secondary analysis of the 2016 Ethiopia Demographic and Health Survey (EDHS). A total of 9,807 weighted under-five children se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The Ethiopian government is working to reduce child deaths and reforms have been made in recent years. In the rural part of Ethiopia, maternal complications during childbirth, immediate exclusive breast-feeding, birth interval, maternal socioeconomic characteristics, and health service seeking actions, etc., are still major challenges 9 , 10 . In order to prepare and enforce an initiative and take steps to address the burden of newborn deaths in the rural areas of Ethiopia, identification of the enumeration area specific factors on infant mortality is therefore necessary 4 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The Ethiopian government is working to reduce child deaths and reforms have been made in recent years. In the rural part of Ethiopia, maternal complications during childbirth, immediate exclusive breast-feeding, birth interval, maternal socioeconomic characteristics, and health service seeking actions, etc., are still major challenges 9 , 10 . In order to prepare and enforce an initiative and take steps to address the burden of newborn deaths in the rural areas of Ethiopia, identification of the enumeration area specific factors on infant mortality is therefore necessary 4 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…This study found the prevalence of under-five mortality in rural Ethiopia was 6% (60/1000) of death per one thousand live children in rural Ethiopia. This result showed that under-five mortality was less than in the study conducted Previous in rural Ethiopia [ 16 ]. This indicates under-five mortality in rural Ethiopia rate is somewhat declining, and access to and utilization of health care is improving.…”
Section: Discussionmentioning
confidence: 55%
“…Using several literature reviews, region, education of mothers, wealth index of HH, marital status, sex of the child, place of delivery, types of birth, breastfeeding, and source of water and toilet facility [ 4 , 16 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children had higher odds of childhood mortality among pit latrine-type toilet facilities as compared to ush-type toilet facilities. This nding was supported by a study in national study and Nigeria [24,25]. This could explain as a result of ush toilets being available in modern sanitation facilities, diarrhea prevalence has been reduced, reducing the infant death rate as well [26].…”
Section: Discussionmentioning
confidence: 77%